Jasa Titip: Menyingkap Risiko dan Celah Perlindungan Hukum di Indonesia - Setiawan Sinaga, Jaya; Paradeys Fenetiruma, Raymond (Zaaken: Journal of Civil and Business Law, 2025)
As human civilization develops, it also causes changes in aspects of lifestyle, one of which is marked by the emergence of various new business fields. As a relatively new business sector, the practice of entrustment services still does not have specific regulations governing it. This article was written with the aim of describing what entrustment services are like in the eyes of positive law in Indonesia, then describing the risks in entrustment services businesses and providing an analysis of the legal protection provided by referring to the relevant regulations currently available. The approach used is a normative legal approach by exploring several laws and regulations that are still related to entrustment services and then analyzing them so that conclusions can be drawn. The results of the study state that entrustment services as a business sector are in principle an agreement, but have special characteristics. Meanwhile, the legal protection provided is in principle similar to other contract-based business fields